Faktor–Faktor Yang Berhubungan dengan Kecemasan Ibu Hamil Trimester III di UPTD Puskesmas Burnai Mulia Kec Semendawai Timur Kab OKU Timur Tahun 2023 - Undari, Tatik; Puspitasari, erma; Amalia, Riski (NHM PRESS, 2024)
Pregnancy is a sensitive period for women. Hormonal changes as a result of adaptation to the growth and development of the fetus in the womb result in psychological changes. Physical and psychological changes during pregnancy can be a stressor that causes anxiety. The prevalence of anxiety in developed countries is around 7-20% and in developing countries around 20%. In Indonesia, around 8-10% experience anxiety during pregnancy and increase to 13% when delivery is approaching. The aim of this study was to determine the relationship between therapeutic communication, husband support and pregnancy exercise simultaneously with the anxiety of third-trimester pregnant women at the UPTD Puskesmas Burnai Mulia Kec. Semendawai Timur, OKU Timur Regency, 2023. Type and Design This research is quantitative in nature using an analytic survey method with a cross-sectional approach. The population in this study were all third trimester pregnant women who came for check-ups at the UPTD Puskesmas Burnai Mulia, Semendawai Timur District, OKU Timur Regency, totaling 288. The sample used was 74 respondents. Sampling using purposive sampling technique. The results of the univariate analysis obtained from 74 respondents, 17 respondents (23.0%) experienced anxiety and 57 respondents (77.0%) did not experience anxiety. The results of the chi-square statistical test for the therapeutic communication variable ρ value = 0.004, the sumai support variable ρ value = 0.000 and pregnancy exercise ρ value = 0.000 less than α = 0.05 indicating that there is a significant relationship between therapeutic communication, husband support and pregnancy exercise with anxiety for third trimester pregnant women at UPTD Burnai Mulia Health Center, Semendawai Timur District, OKU Timur District in 2023.